PERTIMBANGAN MATERIALITAS SEBAGAI VARIABEL PEMODERASI PENGARUH ETIKA PROFESI DAN KOMPETENSI TERHADAP KETEPATAN PEMBERIAN OPINI AUDITOR - Bharata, I Made Arya Putra; Wiratmaja, I Dewa Nyoman (E-Jurnal Akuntansi, 2017)
The accuracy of giving opinion by the auditor is a determinant of audit quality. High quality audits will provide a level of confidence for users of financial statements. This research was to analyze the consideration of materiality as a moderating variable of ethical influence of the profession and competence on the accuracy of giving opinion by the auditor at Public Accountant office in Bali. The sample of this research was 50 people selected from 81 population using purposive sampling method. The analysis data by moderated regression analysis (MRA). The results showed that professional ethics had a positive effect on the accuracy of giving opinion, which means that the higher level of professional ethics awareness of an auditor tends to increase the accuracy in giving opinion. Competence has a positive effect on the accuracy of giving opinion by the auditor, meaning that the higher the competence of an auditor the audit opinion generated tends to be more appropriate. The ability of an auditor's materiality consideration reinforces the positive effect of professional ethics on the accuracy of giving opinion, this means is the positive effect of professional ethics on the accuracy of giving opinion becomes stronger. The ability of materiality considerations can strengthen the positive influence of competence on the accuracy of giving opinion by the auditor, this means that in the situation an auditor has the ability to consider the materiality, the positive influence of competence on the accuracy of giving opinion becomes stronger.
Keywords: professional ethics; competence; judgment materialitas; accuracy giving opinions